Key to Ptychopteridae (Diptera) larvae of Northern Europe, with notes on distribution and biology - Wiberg-Larsen, Peter; Hansen, Søren Birkholm; Rinne, Aki; Viitanen, Esko; Krogh, Paul Henning (Zootaxa, 2021)
A key to larvae of Ptychopteridae (phantom crane flies) is provided for species inhabiting Northern Europe. The key encompasses seven species, including the previously undescribed larvae of Ptychoptera longicauda (Tonnoir 1919). Larval specimens examined were primarily sampled from sites in Denmark. Larvae were associated with correctly identified adults based on DNA barcode (COI) sequence. In the development of the key, a wide suite of morphological characteristics were examined and evaluated for their utility to separate species. Current distribution maps are provided for all species occurring within Northern Europe. Based on records of larvae from Denmark and Finland, notes on larval habitats are given. We also present flight periods for all species examined during this study. Finally, the status of the enigmatic species Ptychoptera obscura (Peus 1958) is briefly discussed.